Can Devaluation Cause Perverse Effects if the Macroeconomy is Stable? (The Pakistan Development Review, 1994)
The theoretical literature on devaluation has involved an appeal to the Correspondence Principle for many years. In the early work, it was noted that a devaluation would improye the trade balance only if the Marshall-Lerner condition held, and this restriction was also necessary and sufficient for stability in the foreign exchange market. Thus, the presumption of economic stability precluded the perverse outcome. More recently, analysts have viewed this early work as limited in that it considered only the aggregate demand effects of the exchange rate, and it did not consider more general specifications of dynamics. The more recent work for example, Buffie (1986) and Lizondo and Montiel (1989) involves intermediate imports and a fully specified aggregate supply sector, and this work recognises that there are at least two kinds of perverse results that can follow from devaluation: the balance of payments can worsen, and the level of employment can fall. (This latter outcome is the so-called contractionary devaluation possibility.)